NEOINDUSTRIALIZATION: FACTORS OF SUSTAINABILITY AND INNOVATION - Ekaterina S. Shirokova (Статистика и экономика, 2016)
The article deals with the socio-economic development in the context neoindustrialization. This releases the functional role and the essence of sustainable development. Special attention is givento evaluation of the results of innovation, research activities and the developmentof human capital.